Makna Pasal 28 Uud 1945 terhadap Kebebasan Berserikat dalam Konteks Hubungan Industrial - Nia Kania Winayanti (Jurnal Konstitusi, 2016)
Freedom of association is not the right belongs to certain group but it is belong to every person as a social beings who naturally can not live alone and stand alone, but living in a group of specific communities.In the context of freedom of association for workers / laborers juridically guaranteed by the Constitution through Article 28 . Through its organic regulations, Law number. 21 year 2001 about Trade Union / Labor Union, according to the opinion of the writer this law is too consentrating on the substance of freedom of association in the shaping of workers / laborers organization, so there is a tendency out of the spirit and the purpose of the formation of trade unions / labor unions that promote the creation of the protection of the interests of the workers / laborers, and boils down to the welfare of the workers / laborers.At the level of industrial relations that emphasizes the aspect of Pancasila and Constitution 1945, the concrete is driven to the creation of industrial relations that runs in the balance between the worker / laborer with the company. The spirit and implementation of industrial relations should be clearly reflected in the harmonious relationship between the worker / laborer with the company, in the form of partnerships that are complementary and beneficial, that is created and protected the interests of the workers / laborers and the resulting product and / or service quality and high competitive, as the offerings from the workers to the company in order to create work productivity optimization.